2018
DOI: 10.12659/msm.911594
|View full text |Cite|
|
Sign up to set email alerts
|

Cucurbitacin B Inhibits the Hippo-YAP Signaling Pathway and Exerts Anticancer Activity in Colorectal Cancer Cells

Abstract: BackgroundColorectal carcinoma (CRC) is one of the most frequently diagnosed malignancies. Cucurbitacin B (CuB) is a natural compound isolated from herbs and shows anticancer activity in several cancers.Material/MethodsHere, we analyzed the effects of different CuB concentrations on the proliferative and invasive behaviors of CRC cells using MTT, clonogenic assay, Transwell invasion, and wound healing assays. Flow cytometry was performed to measure the apoptotic effects of CuB on CRC cells. Western blot and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 31 publications
0
18
1
Order By: Relevance
“…These compounds have a broad spectrum of pharmacological activities including antioxidant, anticancer, and antidiabetic. Chai et al reported Cucurbitacin B exerts anticancer activities in colorectal cancer cells by inhibiting YAP protein [146].…”
Section: Function Of Hippo Pathway In Cancersmentioning
confidence: 99%
“…These compounds have a broad spectrum of pharmacological activities including antioxidant, anticancer, and antidiabetic. Chai et al reported Cucurbitacin B exerts anticancer activities in colorectal cancer cells by inhibiting YAP protein [146].…”
Section: Function Of Hippo Pathway In Cancersmentioning
confidence: 99%
“…Two studies demonstrated that CuE inhibits the EGFR/MAPK/ERK signaling pathway in cancer cells (33,34). Recently, CuB was shown to inhibit the Hippo/YAP pathway in human colorectal cancer cell lines (35). These findings lead us to believe that CuE inhibits YAP indirectly through the EGFR/MAPK/ERK and Hippo/YAP signaling pathways in human NSCLC.…”
Section: Discussionmentioning
confidence: 98%
“…Our study is the first to show that CuE suppresses brain metastasis of human NSCLC in a murine model. A recent study showed that cucurbitacin B (another tetracyclic cucurbitane) inhibits the Hippo-YAP signaling pathway in colorectal cancer cells, but included no in vivo data (35). Another study demonstrated that CuE inhibited breast cancer in a mouse model of metastasis by suppressing cell migration and invasion, but the anti-cancer mechanism of CuE was not investigated (18).…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Among various signaling pathways, the Hippo-YAP signaling pathway has been identified to be involved in the regulation of multiple tumors. 29,30 These analyses indicated that the interaction between LATS2 and the Hippo-YAP signaling pathway might underlie the regulatory function of miR-224-3p in the progression of retinoblastoma. Accumulating evidence has suggested that activation of the Hippo-YAP signaling pathway plays an antitumor role in different types of cancer, including gastric cancer, breast cancer, and prostate cancer.…”
Section: Yap/taz Figurementioning
confidence: 97%